Satellite greenness and solar‐induced chlorophyll fluorescence reveal reverse desertification in Gurbantunggut Desert. Issue 2 (9th December 2022) - He, Panxing; Ma, Jun; Ye, Huawei; Han, Zhiming; Ma, Xiaoliang; Alitengbieke, Hali; Shi, Mingjie; Liu, Huixia; Wang, Huanbo; Sun, Zongjiu
Abstract: The desertification reversal is a process of revegetation and natural restoration in fragile dryland areas due to human activities and climate change mediation. Understanding the impact of desertification reversion on terrestrial ecosystems, including vegetation greenness and photosynthetic capacity, is crucial for land policy‐making and carbon‐cycle model improvement. However, the phenomenon of desertification reversal is rarely mentioned in previous studies, which dramatically limits the understanding of vegetation dynamics in the arid area. Therefore, it is of great necessity to investigate the status of desertification reversal on the ecosystem in arid areas. In this study, we first reported the phenomenon of desertification reversion over the southern edge of the Gurbantunggut Desert through the Moderate‐resolution Imaging Spectroradiometer classification map year by year. We discussed the consequences, ways, and causes of desertification reversion. Our results showed that the desertification reversal significantly increased vegetation greenness and photosynthetic capacity, which largely offset the negative impact of desertification on the ecosystem productivity; cropland expansion and grassland's natural restoration were the two main ways of desertification reversal; the improvement of soil‐water condition was an essential environmental factor leading to the phenomenon of reverse desertification. This finding highlights the importance of desertification reversal in the carbon cycle of dryland ecosystems and prove that desertification reversal is an integral part of global and dryland vegetation greening.